Influence of heavier impurity deposition on surface morphology development and sputtering behavior explored in multiple linear plasma devices - D. Nishijima; A. Kreter; M.J. Baldwin; D. Borodin; A. Eksaeva; D. Hwangbo; S. Kajita; M. Miyamoto; N. Ohno; M. Patino; A. Pospieszczyk; M. Rasinski; et al. (Nuclear Materials and Energy, 2019)
Surface morphology development and sputtering behavior of Cr, as a test material, have been explored under He plasma exposure at a low incident ion energy of ∼80 eV in multiple linear plasma devices: PISCES-A, PSI-2, and NAGDIS-II. From comparison of the experiments in these devices, deposition of a small amount of heavier impurities (Mo in NAGDIS-II and Ta in PISCES-A) onto Cr is found to result in the formation of cone structures on the Cr surface due to preferential sputtering, resulting in a significant reduction (up to ∼10 times) in the sputtering yield of Cr due to line-of-sight redeposition onto the neighboring cones. The heavier impurities are thought to originate from a sample holding cap/cover, which can be sputtered by a trace amount of intrinsic impurities (C, O, etc) as well as by Cr ionized in the plasma. It can be concluded from the Cr experiments, as well as additional Be data collected in PISCES-B, that heavier impurity deposition plays a major role in the cone structure formation, while other mechanisms (e.g. surface irregularity and oxide) also exist. Keywords: Impurity deposition, Sputtering, Nanostructure